2017
DOI: 10.3390/atmos8100183
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Public Health: A PRISMA-Compliant Systematic Review

Abstract: (1) Background: Particulate matter increases the risk of respiratory, allergic and oncological diseases in both exposed workers and the general population due to its toxic compounds (e.g., PAHs, gases, heavy metals, microorganisms). The aim of this review is to show the results obtained by our department regarding air pollution's contributions to health damage in both occupationally and non-occupationally exposed people. (2) Methods: This review was performed according to Preferred Reporting Items for Systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Studies on occupational exposure to air pollutants reported that traffic policemen who were exposed to motor vehicle-generated air pollutants, including diesel exhaust particles, for a long period showed a significant decline in respiratory function [2,3]. A systematic review of studies on the health effects of occupational and non-occupational exposure to air pollutants also reported that occupational exposure to air pollution increased the risk of allergic and pulmonary disease [4]. Epidemiological studies to date suggest that exposure to PM induces lung injury and inflammation, promotes airway hyperresponsiveness, and exacerbates asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on occupational exposure to air pollutants reported that traffic policemen who were exposed to motor vehicle-generated air pollutants, including diesel exhaust particles, for a long period showed a significant decline in respiratory function [2,3]. A systematic review of studies on the health effects of occupational and non-occupational exposure to air pollutants also reported that occupational exposure to air pollution increased the risk of allergic and pulmonary disease [4]. Epidemiological studies to date suggest that exposure to PM induces lung injury and inflammation, promotes airway hyperresponsiveness, and exacerbates asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Both benzo[a]pyrene and pyrene are representative PAHs [4], and the coke oven emissions contribute significantly to the severe pollution of volatile organic compounds (VOCs) in the air [5][6][7][8]. Some studies have shown that PAH exposure from the coke plant still poses a health risk for workers and the general population [1,9]. Coke oven workers at risk should be monitored for adverse effects due to long-term exposure [10].…”
Section: Coke Plants and Pahsmentioning
confidence: 99%
“…Due to its multitudinous emission sources, PM 2.5 pollution has gradually become a worldwide environmental problem. PM 2.5 contains some compounds, such as polycyclic aromatic hydrocarbons (PAHs), heavy metals, and microorganisms [1]. Meanwhile, because of its tiny size, PM 2.5 has a long residence time in the atmosphere and can penetrate to the lower airways [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most obvious problems induced by high levels of PM 2.5 exposure is premature death [5]. Numerous epidemiological studies have shown the harmful effects of long-term PM 2.5 exposure on human health [1,2,[6][7][8][9]. Pun et al [6] found that long-term PM 2.5 exposure has a strong relationship with increased mortality from respiratory disease, lung cancer, and cardiovascular disease in US elderly.…”
Section: Introductionmentioning
confidence: 99%